Water splitting by defects: Insights into multinary transition metal oxides for solar water splitting - Shahin, Samar Mohamed Fawzy Adam (AUC Knowledge Fountain, 2017)
With the energy deficiency problem becoming more threatening, the need to find reliable and alternative energy resources is becoming inevitable. Hydrogen gas is considered a good and cleaner alternative due to its green combustion; and it is used in many applications. Accordingly, the use of solar energy in water splitting to produce hydrogen gas is attracting much attention. Finding the optimum semiconducting material that can efficiently absorb sun light and use it in charge carriers’ generation to split water into hydrogen and oxygen is a hot research topic; as many challenges exist in this regard. For instance, wide-bandgap semiconductors have enhanced stability, but absorption limited to the UV region. On the other hand, a lot of the narrow-bandgap semiconductors have poor stability in aqueous electrolytes. In this thesis we explore different effective pathways to overcome the wide band gap problem. In the first part, the fabrication of nanostructured Ti-Nb-Zr MPNTs via simple hard templating anodization method in an electrochemical bath using Formamide-based electrolyte is explained. The formation mechanism and growth model of the MPNTs is discussed using FESEM images. Optical properties are examined using UV-Vis as well as photoelectrochemical properties where the MPNTs have shown 9-fold enhancement in the photocurrent density over the compact counterpart. The MPNTs possess graded refractive index which was confirmed by ellipsometry measurement; and high light scattering owing to their large diameter. In the second part of the thesis, the MPNTs are annealed in three different gases Air, Oxygen and Hydrogen where a 26-fold enhancement was achieved in the H100 compared to Air and O100. XPS, XRD, and Raman scattering suggested the formation of a single mixed oxide under Air and Oxygen atmospheres, while Zr formed a second phase ZrTiO4 under the reducing atmosphere. XPS core spectra confirmed that Hydrogen annealing resulted in formation of valence band tail states and Ti3+ defects. A thorough discussion is presented on the defects present and their contribution to the water splitting process. Finally, CZTS is known to be a narrow-bandgap p-type semiconductor with absorption extending to the visible region. It was synthesized by a solvothermal method, and deposited by electrophoresis on the MPNTs annealed in Hydrogen. Despite of its instability in 1M KOH, a proof of concept was accomplished, as a great photocurrent enhancement was achieved.